Development of a Taokwan Qing Ping Gong Temple-Based Edu-Tourism Program for Introducing Chinese Culture in Makassar - Ria Riski Marsuki; Dian Sari Unga Waru; Andi Filsah Muslimat; Fakhriawan Fathu Rahman; Leni Cahyati; Khafifa Fuji Lestari; Khairil Anwar; Rizqi Awalia Ilma Amir (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This community service activity aims to develop a culture-based educational tourism program at Taokwan Qing Ping Gong Temple as a medium for introducing Chinese culture to the public. This activity is a follow-up to research conducted by students of the Mandarin Language and Chinese Culture Study Program, which analyzed the symbolic meanings of architectural elements, ornaments, and ritual practices at Qing Ping Gong Temple. The method used in this activity was descriptive qualitative with a community service approach. The results show that the educational tourism program was able to improve participants’ understanding of Chinese cultural values, particularly those related to symbolism, philosophy, and ritual practices found at Taokwan Qing Ping Gong. In addition, this activity provided students with contextual learning experiences through an experiential learning approach. This program has the potential to become an innovative culture-based learning model through direct visits, while also strengthening collaboration between higher education institutions and the community in preserving local culture, particularly temples in Makassar City.